Pengaruh Rasio Profitabilitas terhadap Nilai Perusahaan pada PT. Timah Tbk - Putri Wulandari; M. Rimawan; Hanifah Muthiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this research is to examine the influence of . Return on assets, Return on equity, Net profit margin on Price to book value at PT Timah, Tbk for period 2013-2023. The research employs ratio secondary data derived from the company’s annual financial statement, accessed through the official website (www.timah.ubb.ac.id.). To analyze the data, the study applies a series of statistical methods, including classical assumption tests, multiple linear regression analysis, and hypothesis testing, all conducted using SPSS version 23. The results of this study indicate that Return on Assets has a significant partial effect on Price to Book Value, while Return on Equity does not have a significant partial effect on PBV. Meanwhile, Net Profit Margin has a significant partial effect on PBV. Furthermore, ROA, ROE, and NPM have a significant simultaneous effect on PBV at PT Timah Tbk.